2021
DOI: 10.3390/ijerph18031123
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging Analysis Reveals Frontal-Associated Networks in Relation to Individual Resilience Strength

Abstract: Psychological resilience is regarded as a critical protective factor for preventing the development of mental illness from experienced adverse events. Personal strength is one key element of resilience that reflects an individual’s reactions to negative life events and is crucial for successful adaptation. Previous studies have linked unimodal imaging measures with resilience. However, applying multimodal imaging measures could provide comprehensive organization information at the system level to examine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 109 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…In other words, psychological resilience might have improved in the present study because respondents who experienced good sleep quality were able to maintain high functioning in their emotion control spheres. In neuroimaging, psychological resilience is related to the frontal-associated regions, including the mPFC, amygdala, and anterior cingulate cortex ( Hsieh et al, 2021 ). Among these frontal-associated regions, the functional connectivity between the mPFC and the amygdala is involved in sleep and emotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, psychological resilience might have improved in the present study because respondents who experienced good sleep quality were able to maintain high functioning in their emotion control spheres. In neuroimaging, psychological resilience is related to the frontal-associated regions, including the mPFC, amygdala, and anterior cingulate cortex ( Hsieh et al, 2021 ). Among these frontal-associated regions, the functional connectivity between the mPFC and the amygdala is involved in sleep and emotion.…”
Section: Discussionmentioning
confidence: 99%
“…This acts as a protective factor preventing the worsening of depressive symptoms ( Chang et al, 2023a ). Some studies have reported that several brain regions are involved in psychological resilience, including the medial prefrontal cortex (mPFC), which functions as a mechanism for psychological resilience ( Bremner, 2007 ; Menon and Uddin, 2010 ; Hsieh et al, 2021 ; Chang et al, 2023b ). However, the state of psychological resilience in older adults with MCI has not been described; understanding this state can help develop supportive mental health measures.…”
Section: Introductionmentioning
confidence: 99%
“…Although the existing interventions seem to be effective for promoting resilience of breast cancer patients, the current evidences are still in the preliminary research stage and the quality of them were not high. Recently, more and more studies have shown that in addition to social and psychological factors, biological mechanisms such as the amygdala, hippocampus, ventral striatum and frontal-associated regions of the brain are related to resilience strength [11,59]. An improved understanding of the biological mechanisms-based intervention could reveal novel therapeutic targets and help clarifying which psychosocial interventions can improve the psychological elasticity of breast cancer patients [60].…”
Section: Discussionmentioning
confidence: 99%
“…For the preprocessing of the functional images, we employed the CONN toolbox 18a 3 and SPM 12 4 within Matlab (The MathWorks, Inc., Natick, MA, United States). Our preprocessing protocol was adapted from Geerligs and Tsvetanov's ( 2017) study (see also Hsieh et al, 2021).…”
Section: Functional Mri Image Preprocessingmentioning
confidence: 99%